Environmental Education to Mitigate Environmental Decay and Promote Sustainable Development - Tonia Grace Ganta K. Vijaya Rachel SatyaRaoUppuleti (International Journal of Agricultural Sciences, 2018)
At Present our Planet is grappling with disastrous consequences of man-made environmental problems such as industrialization, urbanization, over-exploitation of natural resources, disruption of natural ecological balances, destruction of a multitude of animal and plant species for economic reasons, etc. It is observed that most of our environmental problems are manifestations of our developmental activities. Although there is no dearth of legislations on environmental protection in India, it is clearly evident that the enforcement of these legislations has been far from satisfactory. The present study tries to establish education as a useful tool for environmental conservation and sustainable development, ensuring clean air to breathe, safe drinking water and adequate supplies of clean renewable energy. This paper is mostly based on secondary data from books, research articles, periodicals and websites. It discusses the role of teacher and school in the protection of environment and promotion of sustainable development by bringing awareness on the efficient and responsible usage of the natural resources namely air, water, land, soil, forests, rivers, oceans etc. It tries to expound the ways and means to sensitize students and make them environment conscious in order to build a vibrant, healthy and pollution free India as future citizens.